Cannabis Use and Fetal Growth in Pregnant Women With Diabetes [18L]. (May 2018) - Hamilton, Owen J. C.; Fowose, Mobolaji; Colditz, Graham; Tuuli, Methodius G.; Carter, Ebony B.
Abstract : INTRODUCTION: Cannabis use during pregnancy is associated with lower birth weight, but little is known about the impact of prenatal cannabis use in women with co-morbidities. Our objective was to examine the association between cannabis use and birthweight in women with pre-existing and gestational diabetes. METHODS: We performed a retrospective cohort study at the Center for Diabetes and Pregnancy at Barnes Jewish Hospital from 2012 to 2016. Women who self-reported cannabis use or had positive maternal or infant drug screens for cannabinoids were compared with those who did not. The primary outcome was large for gestational age (LGA) defined as birthweight >90 percentile. Secondary outcomes were mean birthweight and small for gestational age (SGA, birthweight <10 percentile). Outcomes were compared between women who used cannabis and those who did not. Logistic regression was used to control for potential confounders. RESULTS: Of 298 women who received care during the study period, 12.8% (38) used prenatal cannabis. Women who used cannabis were more likely to have a history of depression and use tobacco. Birthweight was significantly lower in women who used cannabis (2, 732 versus 3, 170 g; P <.003). Women who used cannabis prenatally were 78% less likely to have babies who were LGA (5.3% versus 19.2%, aOR 0.22, 95% CI 0.05–0.98) after controlling for tobacco use. There was no significant difference in SGA. CONCLUSION: Women with diabetes who use cannabis during pregnancy have lower rates of LGA. Larger prospective studies are needed to determine the impact of prenatal cannabis use on maternal, neonatal, and childhood behavioral outcomes in women with diabetes.